The experiences and attitudes of students and lectures regarding peer physical examination in the Faculty of Health Sciences at the University of the Free State - Hattingh, Maryna Getruida Maria (University of the Free State, 2017)
Health professions students use peer physical examinations (PPE) for the purpose of training globally, but in many institutions no formal policy or guidelines exists. There are many benefits of the use of PPE e.g. students are readily available to practise on, students need not to be financially compensated and it has proven to increase students’ clinical skills and confidence, but some students may not want to participate in PPE for various reasons like religion, culture etc. Peer physical examination is the physical examination of a student by a fellow student to enhance his/her clinical skills. This is done under the supervision of a professional person or lecturer. Currently no policy or guidelines regarding peer physical examination exists in the Faculty of Health Sciences (FoHS) at the University of the Free State (UFS) and it is required from the students to participate in peer physical examination during their studies. An in-depth study was conducted to establish the attitudes and experiences of students and lecturers regarding the use of PPE in the FoHS using focus group interviews with students and lecturers. The content of a PPE policy for the FoHS at the UFS was explored with the second question of the focus group interviews. The study was done in the field of Health Professions Educations in the domain of management and leadership and wanted to provide a guideline that may be used to direct students and lecturers when participating in PPE and to explore what is needed to be included in the content of a PPE policy. A qualitative research design was followed with three focus group interviews as data collection method and the compilation of an extensive literature review on the topic. One focus group was with lecturers of all three schools in the FoHS of the UFS who participate in teaching students’ clinical skills and surface anatomy and the other two with students from all three Schools in the FoHS, UFS. Data were transcribed verbatim by the researcher and themes, categories and subcategories identified. Five themes were identified from the collected data. The identified themes, categories and subcategories were compared and discussed with the findings and recommendations of an extensive literature review in mind. The literature review provided a contextual and conceptual understanding of PPE and the benefits and pitfalls associated with the use of it. Perspectives on the use of PPE in different professions were discussed as well as the advantages and disadvantages of the introduction of a policy on PPE at various universities globally. The identified themes were: • Value of PPE • Ethical considerations when using PPE • Student safety • Student concerns • Miscellaneous. The majority of participants agreed that the use of PPE is beneficial to students. The participants agreed participation in PPE increase competence levels in clinical skills, improve confidence and communication skills and assist them to act professionally. Some participants were concerned about educator supervision when practising on peers and some felt that flipping the classroom will benefit students and lecturers as less time will be spent on lecturing and more on the actual practising of the various clinical skills. This study provided recommendations on the content of a PPE policy for the use of PPE from the perspective of health profession students and lecturers from the FoHS at the UFS. The results may be used as guidelines to formulate a PPE policy for the FoHS at the UFS.

Wêreldwyd maak gesondheidsorg studente gebruik van portuurgroep fisieke ondersoeke (PPE), maar in baie instellings bestaan daar geen formele beleid of riglyne daaroor nie. Daar is baie voordele daaraan om van PPE gebruik te maak; bv. daar is altyd studente beskikbaar om op te oefen: dit is nie nodig om studente finansieel te vergoed nie en dit is bewys dat dit studente se kliniese vaardighede en selfvertroue verbeter, maar nie alle studente wil deelneem aan PPE nie. Daar is verskeie redes daarvoor, soos geloof, kultuur ens. PPE is die fisieke ondersoek van ‘n student deur ‘n ander student om sy/haar kliniese vaardigheid te verbeter. Dit word gedoen onder toesig van ‘n professionele persoon of dosent. Tans in die Fakulteit Gesondheidswetenskappe (FGW) aan die Universiteit van die Vrystaat (UV) bestaan daar geen beleid of riglyne met betrekking tot portuurgroep fisieke ondersoeke nie, maar dit word van studente vereis om mee te doen daaraan gedurende hulle studies. Deur gebruik te maak van fokusgroep onderhoude met die studente en dosente van die FGW is ‘n diepgaande studie gedoen om vas te stel wat die houding en ervaring van studente en dosente is in verband met die gebruik van PPE. Die tweede vraag van die fokusgroep onderhoude het gehandel oor die inhoud van ‘n PPE beleid vir die FGW van die UV. Hierdie studie is geleë in die veld van Gesondheidsorg-onderwys in die domein bestuur en leierskap, en poog om riglyne te verskaf aan studente en dosente aangaande deelname aan PPE en ook te bepaal wat moontlik ingesluit moet word in die inhoud van ‘n portuurgroep fisieke ondersoek beleid. ‘n Kwalitatiewe navorsing ontwerp is gevolg met drie fokusgroep onderhoude as data insamelingsmetode asook die samestelling van ‘n uitgebreide literatuuroorsig van die onderwerp. Een fokusgroep onderhoud is gehou met deelnemers uit die geledere van die dosente van die drie verskillende skole binne die FGW, UV wat kliniese vaardighede of oppervlak anatomie doseer en die ander twee met studente van die drie verskillende Skole aan die FGW, UV. Ingesamelde data is deur die navorser verbatim getranskribeer en temas, kategorieë en sub-kategorieë geïdentifiseer. Vyf temas is geïdentifiseer uit die versamelde data. Die temas, kategorieë en sub-kategorieë is vergelyk en bespreek met die bevindinge en aanbevelings van die uitgebreide literatuuroorsig in gedagte. Die literatuurstudie fokus op die kontekstualisering en konseptualisering van PPE en die geassosieerde voor- en nadele van die gebruik daarvan. Perspektiewe op die gebruik van PPE in verskillende professies is bespreek tesame met die voor en nadele wat die inwerkingstelling van ‘n beleid op PPE aan verskeie universiteite wêreldwyd inhou. Die geïdentifiseerde temas is: • Die waarde van PPE • Etiese oorwegings wanneer PPE gebruik word • Veiligheid van studente • Bekommernisse van studente • Allerlei. Die meerderheid deelnemers het saamgestem dat die gebruik van PPE tot die studente se voordeel is. Deelnemers het saamgestem dat deelname aan PPE die studente se bevoegdheid in kliniese vaardighede verbeter asook hul selfvertroue en kommunikasie vaardighede. Dit help hul ook om professioneel op te tree. Sommige van die deelnemers was bekommerd oor die toesig van die dosente wanneer daar op die portuurgroep geoefen word en voel dat om die klas om te keer (flipping the classroom) tot voordeel van die beide die studente en dosente sal wees aangesien minder tyd spandeer sal word op lesings en meer op die in-oefening van die verskillende kliniese vaardighede. Aanbevelings is gemaak in verband met die inhoud van ‘n beleid op portuurgroep fisieke ondersoek vanaf die perspektief van gesondheidsorg studente en dosente van die FGW, UV. Die resultate kan moontlik as riglyn gebruik word om ‘n beleid te formuleer op die gebruik van portuurgroep fisieke ondersoek vir die FGW, UV.
Dissertation (M.HPE. (Health Professions Education))--University of the Free State, 2017
Keywords: Peer physical examination; Guidelines/policy; Health professional students; Focus group interviews; Qualitative research design.